Industrial hemp (Cannabis sativa L.) adapts to cadmium stress by reshaping rhizosphere fungal community - Tingting Feng; Zhuang Meng; Huifen Li; Guohui Chen; Chang'e Liu; Kailei Tang; Jinquan Chen (Science of The Total Environment, 2024)

Cascaded reservoirs promote phosphorus bioavailability of surface sediments in the Upper Mekong River - Zhengjian Yang; QiFeng Min; Xiaojuan Guo; Congfeng Wang; Bi'’e Yan; Xiaoling Li; Defu Liu; Jun Ma; Andreas Lorke (Science of The Total Environment, 2024)

Improvement of soil nutrient cycling by dominant plants in natural restoration of heavy metal polluted areas - Ting Li; Sichen Wang; Luoqi Zhao; Xinqi Yuan; Yuhan Gao; Denggao Fu; Chang'e Liu; Changqun Duan (Environmental Research, 2024)

Biological invasion is eroding the unique assembly of island herpetofauna worldwide - Weishan Tu; Yuanbao Du; Yoel E. Stuart; Yanxia Li; Yanping Wang; Qingfa Wu; Baocheng Guo; Xuan Liu (Biological Conservation, 2024)

Ameliorating the detrimental effects of chromium in wheat by silicon nanoparticles and its enriched biochar - Li Jia; Yue Song; Fangfang You; Sujun Wang; Umm e Rabiya; Xing Liu; Liping Huang; Liye Wang; Waqas ud Din Khan (Science of The Total Environment, 2024)

Recent selection and introgression facilitated high-altitude adaptation in cattle - Yang Lyu; Fuwen Wang; Haijian Cheng; Jing Han; Ruihua Dang; Xiaoting Xia; Hui Wang; Jincheng Zhong; Johannes A. Lenstra; Hucai Zhang; Jianlin Han; David E. MacHugh; et al. (Science Bulletin, 2024)

Dissolved ammonia catalyzes proto-dolomite precipitation at Earth surface temperature - Ruirui Meng; Zuozhen Han; Xiao Gao; Yanyang Zhao; Chao Han; Yu Han; Renchao Yang; Shuangjian Li; Fang Liu; Maurice E. Tucker; Yanjing Chen (Earth and Planetary Science Letters, 2024)

Polyacrylonitrile nanofibrous mat modified with cysteamine and ionic liquid as a recyclable and efficient adsorbent for selective removal of sulfonamides and Cu(II) from aqueous solution: Roles of multi-function adsorption - Hongli Liu; Yuanyuan Dai; Di Wu; Gaoran Zhang; Yongjun Wu; Li-e Liu; Ningge Jian (Chemical Engineering Journal, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Oxygen levels differentially attenuate the structure and diversity of microbial communities in the oceanic oxygen minimal zones - Jiaqian Li; Ningdong Xie; Xiuping Liu; Mohan Bai; Dana E. Hunt; Guangyi Wang (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

From lake to fisheries: Interactive effect of climate and landuse changes hit on lake fish catch? - Shan-e-hyder Soomro; Muhammad Waseem Boota; Haider M. Zwain; Majid Rasta; Caihong Hu; Chengshuai Liu; Yinghai Li; Ao li; Jijun Chen; Chunyun Zhu; Sher Ali; Jiali Guo; et al. (Environmental Research, 2024)

What is the character of N deposition and its proportion to NH3 and NOX inside horticultural greenhouse? - Tiantian Miao; Huan Liu; Yu'e Li; Yunfan Wan; Tianjing Ren; Andong Cai; Bin Wang (Environmental Pollution, 2024)

LLZTO crosslinks form a highly stretchable self-healing network for fast healable all-solid lithium metal batteries - Yingxin Zhang; Xiaohui Yu; Xiaoxiao Li; Jianguo Ren; Peng He; Chao Zhang; Cuiqing Teng; Yue-E Miao; Tianxi Liu (Chemical Engineering Journal, 2024)

Niche similarity accompanying COI genetic differentiations in asexual and sexual Corbicula lineages within East and Southeast Asia - Yangxin Tang; Jie Pi; Neil E. Coughlan; Linwei Liu; Xinhua Liu; Jianguo Xiang; Deliang Li (Hydrobiologia, 2024)

Environmentally-friendly alkaline ionized water pretreatment and hydrolysis of macroalga via microwave-assisted heating to improve monosaccharide yield for bioethanol production - Wei-Hsin Chen; Li-Xuan Liu; Kuan Shiong Khoo; Herng-Kuang Sheen; Eilhann E. Kwon; Ayyadurai Saravanakumar; Jo-Shu Chang (Process Safety and Environmental Protection, 2024)

A fast microbial nitrogen-assimilation technology enhances nitrogen migration and single-cell-protein production in high-ammonia piggery wastewater - Qian Lu; Huankai Li; Hui Liu; Zhimin Xu; Pascal E. Saikaly; Wenxiang Zhang (Environmental Research, 2024)

Evidence of autotrophic direct electron transfer denitrification (DETD) by Thiobacillus species enriched on biocathodes during deep polishing of effluent from a municipal wastewater treatment plant - Haoyong Li; Yuhao Xu; He Dong; Jie Min; Haiyu Xu; Dezhi Sun; Xinying Liu; Yan Dang; Bin Qiu; Thomas Mennella; Dawn E Holmes (Chemical Engineering Journal, 2024)

Appraisal of Urban Waterlogging and Extent Damage Situation after the Devastating Flood - Shan-e-hyder Soomro; Muhammad Waseem Boota; Xiaotao Shi; Gul-e-Zehra Soomro; Yinghai Li; Muhammad Tayyab; Caihong Hu; Chengshuai Liu; Yuanyang Wang; Junaid Abdul Wahid; Mairaj Hyder Alias Aamir Soomro; Jiali Guo; et al. (Water Resources Management, 2024)

Fault control on sedimentation in the southern gentle slope of the Dongying Sag, Bohai Bay Basin - Hong Chen; Shaohua Xu; Chang'e Cai; Wenliang Shang; Jinxin Mao; Zhengjian Xu; Xiaogang Li; Jianping Liu; Nanxin Yin; Kaitong Luo; Chao Lei; Runchao Wang; et al. (Marine and Petroleum Geology, 2024)

Isomer-specific cardiotoxicity induced by tricresyl phosphate in zebrafish embryos/larvae - Xun’e Yi; Haiyu Qin; Guangyu Li; Ren Kong; Chunsheng Liu (Journal of Hazardous Materials, 2024)

Self-assembly of cascade nanoenzyme glucose oxidase encapsulated in copper benzenedicarboxylate for wearable sweat-glucose colorimetric sensors with smartphone readout - Binghua Fan; Yongjun Wu; Hongchao Guo; Fei Yu; Li-e Liu; Songcheng Yu; Jia Wang; Yilin Wang (Analytica Chimica Acta, 2024)

Machine learning framework develops neutrophil extracellular traps model for clinical outcome and immunotherapy response in lung adenocarcinoma - A. Xuan Han; B. Yaping Long; C. Yao Li; D. Di Huang; E. Qi Xiong; F. Jinfeng Li; G. Liangliang Wu; Qiaowei Liu; G. Bo Yang; H. Yi Hu (Apoptosis, 2024)

Phylogenetic origin of an insect fauna at the boundary of the Palaearctic and Oriental realms: Evidence from ‘site‐based’ mitogenomics - Rui‐E Nie; Lu‐Lu Li; Anderson Feijó; Mei‐Xia Yang; Ming Bai; Thomas J. Creedy; Xu Jin; Jia‐Sheng Hao; Yong‐Ying Ruan; Hua‐Xi Liu; Beulah H. Garner; Ladislav Bocak; et al. (Journal of Biogeography, 2024)
Aim Knowledge of taxonomy and species distributions in highly diverse lineages of invertebrates remains too incomplete for the study of biogeographical patterns at the global scale. This limits the understanding of processes leading to the formation and maintenance of boundaries between major biogeographical realms. Site‐based metagenomic approaches may provide an alternative source of data for inference of historical processes of in situ speciation and interchange among biogeographical regions. We applied the methodology to explore the historical biogeography of the Qinling Mountains at the boundary of the Oriental and Palaearctic regions. Location The focal area in the Qinling Mountains; sites in Borneo, Panama, and Spain, representing the Oriental, Neotropical and Palaearctic faunas. Time Period Contemporary. Major Taxa Studied Chrysomelidae, a group of ~40,000 species with worldwide distribution. Methods Mass‐trapped insects were subjected to deep Illumina DNA sequencing and mitochondrial genome assembly, followed by phylogenetic analysis and historical biogeographical inference on a dated tree. The methodology produced 622 mitogenomes (304 newly sequenced) each representing a morphologically distinct species. Results Ancestral area reconstruction revealed that the Qinling fauna is a composite of distinct clades that, respectively, have Oriental or Palaearctic ancient origins, while in situ speciation and local clade formation were limited. The global diversity of Chrysomelidae consists of regionalised deep clades at the level of the major zoogeographic realms, which remain recognisable where these realms abut in the Qinling mountains. Yet, the Qinling fauna is clearly distinct from the source areas although local lineage ages are generally Main Conclusions The Qinling fauna is a composite of clades that have either Oriental or Palaearctic origin, indicating the important role of immigration at the realm boundary. Global site‐based phylogenetic analyses based on metagenomic sequencing can address previously intractable questions about the historical biogeography of poorly studied groups even without a fully developed taxonomy.

Activation of Notch Signaling Pathway is involved in Extracellular Matrix Degradation in human induced pluripotent stem cells chondrocytes induced by HT-2 toxin - Peilin Meng; Huan Liu; Li Liu; Yan Wen; Feng'e Zhang; Yanan Zhang; Yumeng Jia; Yingang Zhang; Feng Zhang; Xiong Guo (Food and Chemical Toxicology, 2024)

Research on runoff process vectorization and integration of deep learning algorithms for flood forecasting - Chengshuai Liu; Wenzhong Li; Caihong Hu; Tianning Xie; Yunqiu Jiang; Runxi Li; Shan-e-hyder Soomro; Yuanhao Xu (Journal of Environmental Management, 2024)

Interpretable baseflow segmentation and prediction based on numerical experiments and deep learning - Qiying Yu; Chen Shi; Yungang Bai; Jianghui Zhang; Zhenlin Lu; Yingying Xu; Wenzhong Li; Chengshuai Liu; Shan-e-hyder Soomro; Lu Tian; Caihong Hu (Journal of Environmental Management, 2024)

Effect of Ba2+ on the biomineralization of Ca2+ and Mg2+ ions induced by Bacillus licheniformis - Huaxiao Yan; Xiaofei Zhu; Zhenjiang Li; Zhiyong Liu; Shengping Jin; Xiaotong Zhou; Zuozhen Han; Jusun Woo; Long Meng; Xiangqun Chi; Chao Han; Yanyang Zhao; et al. (World Journal of Microbiology and Biotechnology, 2024)

New Record Ocean Temperatures and Related Climate Indicators in 2023 - Lijing Cheng; John Abraham; Kevin E. Trenberth; Tim Boyer; Michael E. Mann; Jiang Zhu; Fan Wang; Fujiang Yu; Ricardo Locarnini; John Fasullo; Fei Zheng; Yuanlong Li; et al. (Advances in Atmospheric Sciences, 2024)
The global physical and biogeochemical environment has been substantially altered in response to increased atmospheric greenhouse gases from human activities. In 2023, the sea surface temperature (SST) and upper 2000 m ocean heat content (OHC) reached record highs. The 0–2000 m OHC in 2023 exceeded that of 2022 by 15 ± 10 ZJ (1 Zetta Joules = 10 21 Joules) (updated IAP/CAS data); 9 ± 5 ZJ (NCEI/NOAA data). The Tropical Atlantic Ocean, the Mediterranean Sea, and southern oceans recorded their highest OHC observed since the 1950s. Associated with the onset of a strong El Niño, the global SST reached its record high in 2023 with an annual mean of ∼0.23°C higher than 2022 and an astounding > 0.3°C above 2022 values for the second half of 2023. The density stratification and spatial temperature inhomogeneity indexes reached their highest values in 2023.

How effective is twitter (X) social media data for urban flood management? - Shan-e-hyder Soomro; Muhammad Waseem Boota; Haider M. Zwain; Gul-e-Zehra Soomro; Xiaotao Shi; Jiali Guo; Yinghai Li; Muhammad Tayyab; Mairaj Hyder Alias Aamir Soomro; Caihong Hu; Chengshuai Liu; Yuanyang Wang; et al. (Journal of Hydrology, 2024)

Whole transcriptome mapping reveals the lncRNA regulatory network of TFP5 treatment in diabetic nephropathy - Hongyan Luo; Lirong Yang; Guoqing Zhang; Xi Bao; Danna Ma; Bo Li; Li Cao; Shilu Cao; Shunyao Liu; Li Bao; Jing E; Yali Zheng (Genes & Genomics, 2024)

Biological characteristics of Cordyceps militaris single mating-type strains - Xiu’E Li; Xin Wang; Fengji Liang; Zhaoxin Wang; Wenshuo Liu; Yupeng Ge; Shude Yang; Yu Liu; Yin Li; Xianhao Cheng; Weihuan Li (Archives of Microbiology, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Changes in soil microbe-mediated carbon, nitrogen and phosphorus cycling during spontaneous succession in abandoned Pb Zn mining areas - Sichen Wang; Xinqi Yuan; Ting Li; Jie Yang; Luoqi Zhao; Duanyang Yuan; Zhaolai Guo; Chang'e Liu; Changqun Duan (Science of The Total Environment, 2024)

Advances in wastewater analysis revealing the co-circulating viral trends of noroviruses and Omicron subvariants - Teresa Kumblathan; Yanming Liu; Mary Crisol; Xiaoli Pang; Steve E. Hrudey; X. Chris Le; Xing-Fang Li (Science of The Total Environment, 2024)

Recycling of waste polyethylene in asphalt and its performance enhancement methods: A critical literature review - Hui Li; Yuzhao Han; E Guangxun; Yang Sun; Lei Wang; Xufei Liu; Jiaxing Ren; Zhijie Lin (Journal of Cleaner Production, 2024)

Aligning nature-based solutions with ecosystem services in the urban century - Roy P. Remme; Megan Meacham; Kara E. Pellowe; Erik Andersson; Anne D. Guerry; Benjamin Janke; Lingling Liu; Eric Lonsdorf; Meng Li; Yuanyuan Mao; Christopher Nootenboom; Tong Wu; et al. (Ecosystem Services, 2024)

Oral delivery of berberine by liver-targeted zwitterionic nanoparticles to overcome multi-intestinal barriers and extend insulin treatment duration - Yuhong Ma; Caihua Li; Fuwei Han; Yunzhu Liu; Umm E Hani; Yinan Zhong; Dechun Huang; Wei Chen; Hongliang Qian (Chemical Engineering Journal, 2024)

Peacock flaunting tail inspired-multiple interactions between black phosphorene and glass powder with safety shield fire of epoxy resin - Kunxin Wang; Guoming Yuan; Zhijun Liu; Hui Yang; Yang Li; Xiu-e Li; Kun Wu; Jun Shi (Chemical Engineering Journal, 2024)

Global multifaceted biodiversity patterns, centers, and conservation needs in angiosperms - Ao Luo; Yaoqi Li; Nawal Shrestha; Xiaoting Xu; Xiangyan Su; Yichao Li; Tong Lyu; Kilara Waris; Zhiyao Tang; Xiaojuan Liu; Luxiang Lin; Yongsheng Chen; et al. (Science China Life Sciences, 2024)

Quantitative prediction and spatial analysis of structural fractures in deep shale gas reservoirs within complex structural zones: A case study of the Longmaxi Formation in the Luzhou area, southern Sichuan Basin, China - Cunhui Fan; Shan Nie; Hu Li; Ahmed E. Radwan; Qingchuan Pan; Xiangchao Shi; Jing Li; Yongyang Liu; Yi Guo (Journal of Asian Earth Sciences, 2024)

Soybean-processing wastewater as an electron donor for denitrification - Yue Ma; Chong Tan; Songyun Chen; Haiyun Zhang; Fei Liu; Xu Peng; Mo Li; Yongming Zhang; Bruce E. Rittmann (International Biodeterioration & Biodegradation, 2024)

Effects of Nitrogen and Phosphorus Limitation on the Growth and Phosphorus Allocation of Alfalfa (Medicago sativa L.) - Yafei Hu; Cheng Qian; Xin Zhao; Junlin Li; Lin Wang; Dalin Liu; Xin’e Li (Journal of Soil Science and Plant Nutrition, 2024)

PD-L1 expression guidance on sintilimab versus pembrolizumab with or without platinum-doublet chemotherapy in untreated patients with advanced non-small cell lung cancer (CTONG1901): A phase 2, randomized, controlled trial - Si-Yang Maggie Liu; Jie Huang; Jia-Yi Deng; Chong-Rui Xu; Hong-Hong Yan; Ming-Yi Yang; Yang-Si Li; E-E Ke; Ming-Ying Zheng; Zhen Wang; Jia-Xin Lin; Bin Gan; et al. (Science Bulletin, 2024)

Soil microbial communities' contributions to soil ecosystem multifunctionality in the natural restoration of abandoned metal mines - Ting Li; Sichen Wang; Chang'e Liu; Yadong Yu; Mingming Zong; Changqun Duan (Journal of Environmental Management, 2024)

Transient heat transfer simulation, sensitivity analysis, and design optimization of shallow ground heat exchangers with hollow-finned structures for enhanced performance of ground-coupled heat pumps - Basher Hassan Al-Kbodi; Taha Rajeh; Mohamed E. Zayed; Yang Li; Jun Zhao; Jiahui Wu; Yuanyuan Liu (Energy and Buildings, 2024)

Quaternary ammonium salt coated air filter for bioaerosol removal from building indoor air - Huixin Jiang; Kai Li; David E. Graham; Attelia Hollander; Mariappan P. Paranthaman; M. Muneeshwaran; Xiaoli Liu; Merlin Theodore; Tolga Aytug; Keju An; Kashif Nawaz (Building and Environment, 2024)

Simple, fast and eco-friendly micro-solid phase extraction based on thiol and ionic liquid bi-functional nanofibers membrane for the determination of sulfonamides in environmental water - Ningge Jian; Yuanyuan Dai; Hongli Liu; Niu Wu; Li-e Liu; Di Wu; Yongjun Wu (Analytica Chimica Acta, 2024)

Effects of konjac glucan-nan/low-acyl gellan edible coatings loaded thymol-β-cyclodextrin microcapsules on postharvest blueberry - Jie Ding; Chunyan Liu; Peng Huang; Hongying Li; Yan Liu; Dur E. Sameen; Yuwei Zhang; Yaowen Liu; Wen Qin (Food Chemistry, 2024)

Bacterial, short-chain fatty acid and gas profiles of partially hydrolyzed guar gum in vitro fermentation by human fecal microbiota - Xiong-E Pi; Hao Fu; Xiao-Xia Yang; Zai-Chun Yu; Wei-Lin Teng; Yinjun Zhang; Xue-Wei Ye; Hui Hui Quan; Li-Zhi Lu; Wei Liu (Food Chemistry, 2024)

Stress ratio sensitivity—a novel parameter for evaluating the shearing-based structural characteristic of loess - Meng Yao; Hui-e Chen; Hui Li; Qing wang; Yan Han; Qingbo Yu; Yibo Liu (Bulletin of Engineering Geology and the Environment, 2024)